Kidney histology in streptozotocin-induced diabetic male Wistar rats treated with combined extract of temulawak rhizome and belimbing wuluh fruit - KARTIAWATI ALIPIN; EMA PURNAMA SARI; MADIHAH MADIHAH; TIA SETIAWATI; NINING RATNINGSIH; DESAK MADE MALINI (Smujo International, 2017)
Alipin K, Sari EP, Madihah, Setiawati T, Ratningsih N, Malini DM. 2017. Kidney histology in streptozotocin-induced diabetic male Wistar rats treated with combined extract of temulawak rhizome and belimbing wuluh fruit. Nusantara Bioscience 9: 312-317. Complications that are occurred in patients with Diabetes Mellitus usually followed by kidney damage. Temulawak (Curcuma xanthorrhiza Roxb.) and belimbing wuluh (Averrhoa bilimbi L.) were traditionally used to decrease blood glucose level. Thus, they were potential as antidiabetic drugs. This study aimed to evaluate the combination of ethanol extracts of temulawak rhizome and belimbing wuluh fruit in repairing kidney damage in diabetic male Wistar rats induced by streptozotocin (STZ). An experimental method using a completely randomized design that consist of seven treatments with three replications. Six treatment groups were injected intraperitoneally with a dose of 60 mg/kg BW STZ, and one group served as a control. The animals which have blood glucose level â‰¥200 mg/dl were stated as diabetic. Furthermore, the animals were treated orally with single extract i.e. temulawak 17.5 mg/kg BW or belimbing wuluh 750 mg/kg BW and combined extracts 383.75 or 767.5 mg/kg BW, as well as glibenclamide 0.45 mg/kg BW as reference, including diabetic rat as positive control and non-diabetic rat as negative control. The results showed that combine extract at dose of 383.75 mg/kg BW treatment repaired the kidney histology, i.e., glomerular diameter and Bowman space width, as well as significantly decreased the necrosis percentage of proximal tubular in diabetic rat compared with positive control group (p<0.05). In conclusion, the combined extract of temulawak rhizome and belimbing wuluh fruit has potent to cure renal failure in diabetic rats induced by streptozotocin.